PENGARUH KETERSEDIAAN FITUR, KEAMANAN DAN KEMUDAHAN TERHADAP KENYAMANAN PENGGUNAAN MOBILE BANKING - K, Felicia Chandra; Dian Wulandari, Oryz Agnu (Jurnal EBI, 2024)
The widespread use of mobile banking in every transaction leads to high user expectations for mobile banking services. This poses a significant challenge for banks to focus on user comfort. This study aims to measure the impact of feature availability, security, and ease of use on the comfort of mobile banking users. The research sample was obtained using a random sampling technique from mobile banking users in Cirebon City, with a total of 100 respondents, and data collection was conducted through a Google Form questionnaire. This study employs quantitative analysis, including outer loading analysis, inner model analysis, discriminant validity test, reliability test, determination coefficient test (R Square), effect size test (F Square), and predictive relevance test (Q Predict).Key words:features, security, userfriendly, comfort, mobile banking.